A note on generalized inverses - Embrechts, Paul; Hofert, Marius (Mathematical methods of operations research (Heidelberg, Germany), 2013)
Motivated by too restrictive or even incorrect statements about generalized inverses in the literature, properties about these functions are investigated and proven. Examples and counterexamples show the importance of generalized inverses in mathematical theory and its applications.